Elevated extracellular particle concentration in plasma predicts in-hospital mortality after severe trauma - Becker, Nils; Franz, Niklas; Eguchi, Akiko; Wagner, Alessa; Sturm, Ramona; Rinderknecht, Helen; Kobayashi, Yoshinao; Iwasa, Motoh; Weber, Birte; Marzi, Ingo; Relja, Borna (Frontiers in Immunology, 2024)
Background: Extracellular particles (EPs), particularly extracellular vesicles, play a crucial role in regulating various pathological mechanisms, including immune dysregulations post-trauma. Their distinctive expression of cell-specific markers and regulatory cargo such as cytokines or micro-ribonucleic acid suggests their potential as early biomarkers for organ-specific damage and for identifying patients at risk for complications and mortality. Given the critical need for reliable and easily assessable makers to identify at-risk patients and guide therapeutic decisions, we evaluated the early diagnostic value of circulating EPs regarding outcomes in severely injured multiple-trauma patients. Methods: Plasma samples were collected from 133 severely injured trauma patients (Injury Severity Score (ISS) ≥16) immediately upon arrival at the emergency department (ED). Patients were categorized into survivors and non-survivors. Injury characteristics and outcomes related to sepsis, pneumonia, or early (<1 day after admission) and late mortality were assessed. Circulating EPs, cytokine profiles, and blood counts of platelets and leukocytes were determined. Receiver operating characteristic analyses were conducted. Results: Despite no significant differences in injury pattern or severity, non-survivors exhibited significantly elevated counts of circulating EPs compared to survivors. The optimal cut-off for EPs < 200 nm indicating non-survivors was 17380/µl plasma, with a sensitivity of 77% and a specificity of 61% in predicting in-hospital mortality. Later non-survivors received significantly higher numbers of units of packed red blood cells [8.54±5.45 vs. 1.29±0.36 units], had higher serum lactate [38.00±7.51vs. 26.98±1.58 mg/dL], significantly lower platelet counts [181.30±18.06 vs. 213.60±5.85 *10³/µL] and lower heart rates [74.50±4.93 vs. 90.18±2.06 beats/minute] upon arrival at the ED compared to survivors. Conclusion: Our results demonstrate the high diagnostic potential of elevated concentrations of circulating EPs <200 nm for identifying patients at risk of mortality after severe trauma. This parameter shows comparable sensitivity to established clinical predictors. Early evaluation of EPs concentration could complement assessment markers in guiding early therapeutic decisions.